How Is Psychological Outcome Related to Knee Function and Return to Sport Among Adolescent Athletes After Anterior Cruciate Ligament Reconstruction?. Issue 7 (June 2019) - Beischer, Susanne; Hamrin Senorski, Eric; Thomeé, Christoffer; Samuelsson, Kristian; Thomeé, Roland
Background: Adult patients who succeed in returning to their preinjury levels of sport after anterior cruciate ligament (ACL) reconstruction have been characterized by a more positive psychological response. It is not known whether this relationship is valid for adolescent athletes. Purpose: To investigate psychological readiness to return to sport, knee-related self-efficacy, and motivation among adolescent (15-20 years old) and adult (21-30 years old) athletes after ACL reconstruction. A further aim was to compare athletes (15-30 years old) who had recovered their muscle function and returned to sport with athletes who had not. Study Design: Case-control study; Level of evidence, 3. Methods: Data were extracted from a rehabilitation-specific register 8 and 12 months after ACL reconstruction. Athletes previously involved in knee-strenuous sport who had undergone primary ACL reconstruction were included. Data comprised psychological patient-reported outcomes and results from 5 tests of muscle function. Comparisons were performed between age groups, between athletes who had and had not recovered their muscle function, and between patients who had returned to sport and not. Results: In all, 384 (50% females) and 271 athletes (52% females) were included at the 8- and 12- month follow-ups, respectively. Enhanced self-efficacy was reported at both follow-ups by adolescents and by athletes who had recovered their muscle function. Athletes who had recovered their muscle function reported higher ( P = .0007) motivation to achieve their goals. Subgroup analyses on patient sex revealed findings similar to those in the main analyses for females but not for males. Moreover, adolescent and adult athletes who had returned to sport reported significantly higher levels on the Knee Self-Efficacy Scale and the ACL–Return to Sport After Injury scale at both follow-ups. Conclusion: Adolescent athletes, especially females, perceived enhanced self-efficacy, had a higher return-to-sport rate, and were more motivated to reach their goals after ACL reconstruction compared with adults. Regardless of age, athletes who had returned to sport and athletes with more symmetrical muscle function had a stronger psychological profile.